PROFIL ASAM LEMAK MINYAK SAWIT SETELAH PROSES PENGGORENGAN IKAN - Harikedua, Silvana Dinaintang; Harikedua, Vera T (Media Teknologi Hasil Perikanan, 2018)
The fatty acid profile of palm oil is presented in this work. The palm oil (control) was rich in palmitic acid (39.01%) and oleic acid (44.50%). The results indicated that fish frying process for about 60 minutes was given little differences fatty acid profiles compared to control palm oil. The major fatty acid in the palm oil after frying fish was palmitic acid (41. 13%) and oleic acid (42.62), and developed the existenceof palmitoleic acid (0.28%), which is not found in control palm oil.